2003
DOI: 10.1109/tip.2003.819307
|View full text |Cite
|
Sign up to set email alerts
|

Soft decoding and synchronization of arithmetic codes: application to image transmission over noisy channels

Abstract: Abstract| This paper addresses the issue of robust and joint source-channel decoding of arithmetic codes. We rst analyze dependencies between the variables involved in arithmetic coding by means of the Bayesian formalism. This provides a suitable framework for designing a soft decoding algorithm that provides high error-resilience. It also provides a natural setting for "soft synchronization", i.e., to introduce anchors favoring the likelihood of "synchronized" paths. In order to maintain the complexity o f th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 26 publications
0
67
0
Order By: Relevance
“…Howard et al observed that by rounding the interval boundaries, one can noticeably decrease the computational cost of AC without significantly degrading the compression performance. In [6], the table-lookup representation was exploited in order to derive a stochastic automaton which is then followed by a convolutional code. Iterative decoding was used at the receiver side.…”
Section: Trellis-based Arithmetic Coding and Decodingmentioning
confidence: 99%
See 2 more Smart Citations
“…Howard et al observed that by rounding the interval boundaries, one can noticeably decrease the computational cost of AC without significantly degrading the compression performance. In [6], the table-lookup representation was exploited in order to derive a stochastic automaton which is then followed by a convolutional code. Iterative decoding was used at the receiver side.…”
Section: Trellis-based Arithmetic Coding and Decodingmentioning
confidence: 99%
“…On the other hand, for a memoryless source with a known probability model, the encoder is entirely characterized by the current interval [low, high) and the value of f ollow. Hence, the encoder state can be represented by (low, high, f ollow) as defined in [6]. The idea is thus to precompute all possible states of the arithmetic encoder such that any source stream may be encoded using table lookups rather than arithmetic operations.…”
Section: A Ac Interpreted As a State Machinementioning
confidence: 99%
See 1 more Smart Citation
“…Performance is further improved if soft information is iteratively exchanged between source and channel decoder. The proposed schemes in [7], [8], [9], [10] consider state machine representation of arithmetic decoding to apply channel decoding techniques like Viterbi, list-Viterbi, and other sequential search techniques. In [7] stack algorithm and M-algorithm was applied for maximum a posteriori (MAP) error correction decoding of arithmetic codes with forbidden symbol.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in [26], the performance of JPEG 2000 decoding based on MAP and maximum likelihood (ML) metrics is analyzed in the case of transmission across the BSC and the AWGN channel. Soft decoding of arithmetic codes with synchronization marker is studied in [27] and applied to the case of image transmission. It is worth pointing out that the techniques introduced in [25]- [27] are being included in the upcoming Part 11 of the JPEG 2000 standard, which addresses the wireless applications of the novel image coding standard.…”
Section: Introductionmentioning
confidence: 99%